გაზეთი "სამუსლიმანო საქართველო" და აჭარის ავტონომიის საკითხი - Manvelidze, Irakli; Iremadze, Gela (Politics / პოლიტიკა; 2018: მეოთხე ნომერი, 2019)
As it can be easily seen in the article propaganda of irreversible autonomy in Adjara was artificially started in the region to make the population believe that autonomy was the only way for welfare and happiness. In the course of events the population of the region rejected the direct government introduced after restoration of jurisdiction of Georgia in 1920. Confrontation between the pro-Georgian and anti-Georgian forces, as well as ideological war set between the political organizations and propagandists extremely aggravated political situation in Adjara. Unfortunately, the Liberation Committee and its printing body agitated the idea of autonomy. Gradually the confrontation acquired the form of fight for autonomy due to the fact, that the fruits of autonomy were considered useful for political ambitions of the mentioned parties. Autonomy was a lever to reach the government seats in the region and was the only way to hit the target. The decision made by Georgian government on closing the newspaper “Muslim Georgia” (and also closure of  ,,Sedai Mileti~) in the second half of 1920 refers to the fact that the information spread by the newspaper didn’t cope with the state interests.
Keywords: Adjara, Autonomy, Political Status, Region, Newspaper.